2005
DOI: 10.1038/sj.onc.1208429
|View full text |Cite
|
Sign up to set email alerts
|

DeltaEF1 is a transcriptional repressor of E-cadherin and regulates epithelial plasticity in breast cancer cells

Abstract: Downregulation of E-cadherin is a crucial event for epithelial to mesenchymal transition (EMT) in embryonic development and cancer progression. Using the EpFosER mammary tumour model we show that during EMT, upregulation of the transcriptional regulator deltaEF1 coincided with transcriptional repression of E-cadherin. Ectopic expression of deltaEF1 in epithelial cells was sufficient to downregulate E-cadherin and to induce EMT. Analysis of E-cadherin promoter activity and chromatin immunoprecipitation identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
585
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 707 publications
(619 citation statements)
references
References 56 publications
(67 reference statements)
12
585
2
3
Order By: Relevance
“…In agreement with these studies, we also found that Snail and Slug mRNA levels were upregulated in our EMT tumors. In addition, we also detected an increase in transcript levels of Zeb1 and Twist, both of which have been shown to directly repress E-cadherin transcription and induce EMT in breast cancer cells in vitro (Eger et al, 2005;Vesuna et al, 2008). Whether Zeb1 and Twist are causally linked to tumor recurrence in a similar manner to Snail will require further investigation.…”
Section: Discussionmentioning
confidence: 72%
“…In agreement with these studies, we also found that Snail and Slug mRNA levels were upregulated in our EMT tumors. In addition, we also detected an increase in transcript levels of Zeb1 and Twist, both of which have been shown to directly repress E-cadherin transcription and induce EMT in breast cancer cells in vitro (Eger et al, 2005;Vesuna et al, 2008). Whether Zeb1 and Twist are causally linked to tumor recurrence in a similar manner to Snail will require further investigation.…”
Section: Discussionmentioning
confidence: 72%
“…Decreased Zeb2 mRNA was observed using five independent Zeb1 shRNAs (Supplementary Figure S9b). Conversely, EpH4-FosER cells expressing ZEB1 40 had increased Zeb2 mRNA in the absence of 4-hydroxyTamoxifen ( Supplementary Figures S9c and d). This indicates that Zeb1 contributes to controlling Zeb2 expression in EpH4-derived cells.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 Ras and TGFβ cooperate to induce and stabilize a mesenchymal switch in EpH4 cells. 21,22,40 Unlike human breast cancer cells where upstream signalling kinases activation is required, 14,16 ectopic Fra-1 expression was sufficient for EMT and tumorigenesis in EpH4 cells. Moreover, Fra-1 increased TGFβ expression and production, similarly to c-Fos and unlike oncogenic Ras, 43 thus TGFβ treatment was not necessary for EMT in EpFra1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc finger E‐box binding protein 1 (ZEB1) and ZEB2 (also known as δEF‐1 and SIP‐1, respectively) are well‐known transcriptional regulators that induce EMT, which plays important roles in both normal physiological and pathological processes (Eger et al ., 2005; Vandewalle et al ., 2005; Zhang et al ., 2015). While ZEB1 and ZEB2 have many similar properties in transcriptional regulation, they are different in their expression profiles, some molecular and biological functions, including regulation of cell differentiation and disease progression (Postigo and Dean, 2000; Wakamatsu et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%